The opposing forces of shear flow and sphingosine-1-phosphate control marginal zone B cell shuttling. Issue 1 (December 2017) - Tedford, Kerry; Steiner, Michael; Koshutin, Stanislav; Richter, Karin; Tech, Laura; Eggers, Yannik; Jansing, Inga; Schilling, Kerstin; Hauser, Anja; Korthals, Mark; Fischer, Klaus-Dieter
Abstract Splenic marginal zone B cells (MZB) shuttle between the blood-filled marginal zone for antigen collection and the follicle for antigen delivery. However, it is unclear how MZBs migrate directionally from the marginal zone to the follicle. Here, we show that murine MZBs migrate up shear flow via the LFA-1 (αLβ2) integrin ligand ICAM-1, but adhere or migrate down the flow via the VLA-4 integrin (α4β1) ligand VCAM-1. MZBs lackingArhgef6 (Pak-interacting exchange factor (αPIX)) or functional LFA-1 are impaired in shuttling due to mislocalization toward the VCAM-1-rich red pulp. Sphingosine-1-phosphate (S1P) signaling through the S1PR3 receptor inhibits MZB migration up the flow, and deletion ofS1pr3 inArhgef6 −/− mice rescues mislocalized MZBs. These findings establish shear flow as a directional cue for MZB migration to the follicle, and define S1PR3 and VCAM-1 as counteracting forces that inhibit this migration. Marginal zone B (MZB) cells shuttle between the marginal zone and lymphoid follicle to capture and present peripheral blood antigens. Here the authors show that shear force, such as blood flow from the sinus around the follicle, is a directional cue that induces MZB migration on ICAM-1, and that S1P signaling inhibits this directional migration.